2018
DOI: 10.1021/acssuschemeng.7b04466
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thermoplastic Cellulose Esters Containing Bulky Moieties and Soft Segments

Abstract: It is still challenging to convert cellulose into melt-processable materials because natural cellulose, which has a strong hydrogen bonding network, degrades before melting. Herein, a series of novel cellulose-based thermoplastics were successfully designed and fabricated by a simple and efficient homogeneous esterification of cellulose in an ionic liquid. Introducing ester substituents containing both bulky moieties and soft segments can improve the mobility of the cellulose chain, and the glass transition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 65 publications
1
65
0
Order By: Relevance
“…21 Recently, Zhang and co-workers have reported that cellulose phenylpropionate derivatives, which have a phenylpropionate unit similar to the structure of cinnamaldehyde, show thermoplasticity and are useful as plastics. 22 However, compared to classical esterification, oxidative esterification reactions are complicated and expected to result in side reactions due to the use of a powerful oxidizer. Furthermore, oxidative esterification has been considered unsuitable for the modification of poorly soluble cellulose in various solvents, including ionic liquids (ILs), 18,23 which are ionic compounds with melting points below 100°C, 24 because they require an excess of the alcohol to prevent the dimerization pathway of the aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…21 Recently, Zhang and co-workers have reported that cellulose phenylpropionate derivatives, which have a phenylpropionate unit similar to the structure of cinnamaldehyde, show thermoplasticity and are useful as plastics. 22 However, compared to classical esterification, oxidative esterification reactions are complicated and expected to result in side reactions due to the use of a powerful oxidizer. Furthermore, oxidative esterification has been considered unsuitable for the modification of poorly soluble cellulose in various solvents, including ionic liquids (ILs), 18,23 which are ionic compounds with melting points below 100°C, 24 because they require an excess of the alcohol to prevent the dimerization pathway of the aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…[ 75 ] To improve these properties as well as processability, fatty acid esters are widely employed. [ 76 ] The hydrophobically modified surface led to significantly decreased water vapor, oxygen, nitrogen, and carbon dioxide permeability. [ 77 ] Surprisingly, cellulose films prepared from NaOH/urea or LiOH/urea solutions have even lower oxygen permeabilities than commercial oxygen barrier films such as poly(vinylidene chloride) and poly(vinyl alcohol).…”
Section: Regeneration Of Cellulose In Different Physical Formsmentioning
confidence: 99%
“…Hydroxyl groups were esterified both with bulky and small substituents, resulting in a relatively low T g from 80 to 160 °C. The resulting materials can be used for common thermoplastic processing without external plasticization …”
Section: Lignocellulosic Biomassmentioning
confidence: 99%
“…The resulting materials can be used for common thermoplastic processing without external plasticization. [47] Besides esterification, cellulose ethers can also display thermoplastic properties. Via hydroxyl group substitution with alcohols, several derivatives such as methyl cellulose, carboxymethyl cellulose, and hydroxypropyl methylcellulose have been produced and commercialized.…”
Section: Approaches For Thermoplastic Processingmentioning
confidence: 99%